Nigerin and ochracenes J−L, new sesquiterpenoids from the marine sponge symbiotic fungus Aspergillus niger. (8th January 2022) - Shang, Ru-Yi; Cui, Jie; Li, Jia-Xin; Miao, Xian-Xian; Zhang, Lu; Xie, Dong-Dong; Zhang, Liang; Lin, Hou-Wen; Jiao, Wei-Hua
Abstract : Four new sesquiterpenoids, nigerin (1 ) and ochracenes J–L (2 –4 ), were isolated from a symbiotic fungus Aspergillus niger of a marine sponge Dysidea sp. collected from the South China Sea. Nigerin (1 ) possesses an unprecedented 1-(3- n -pentyl)-2, 5, 6-trimethyl-cycloheptane carbon skeleton, which represents a new type sesquiterpene scaffold. Ochracenes J–L (2 –4 ) are three new humulane-derived sesquiterpenoids. The structures of 1 –4 were elucidated by a combination of 1D and 2D NMR and HRMS analyses, and their absolute configurations were assigned by Mosher's method and ECD calculations. Among the four isolates, nigerin (1 ) and ochracene J (2 ) showed potent inhibitory activity on the production of nitric oxide (NO) in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages with IC50 values of 8.5 and 4.6 μM, respectively. Graphical abstract: Image 1